Addressing appropriate and inappropriate teacher-student relationships: a secondary education professional development model - Zarra, III, Ernest J. Kern High School District; Zarra, III, Ernest J. (Center for Leadership Equity and Research)
Schools and colleges of education spend very little time on teacher ethics and morality, defaulting to mentor teachers in the hopes that candidates garner what is necessary from them, in order to be successful in the real-world classroom. At a time when the nation is reeling from teacher shortages, vigilancenot expediencymust be maintained as adults are placed into very challenging circumstances with teenagers. However, districts are resorting to creative credentialing, often relying only on state data-bank background checks, thereby placing students at risk. The facts are that lines are blurred today for a variety of reasons between teachers, students, and also coaches and athletes. Sometimes inappropriate behaviors emerge that lead to arrest and imprisonment for teachers, regardless the type of school. Specifically, secondary educators need professional development to assist them in their decision-making, so as to avoid career-ending and life-altering criminal, career, and even emotional and moral mistakes in their relationships with students.